2015
DOI: 10.1016/j.molp.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Panax ginseng UDP-Glycosyltransferases Catalyzing Protopanaxatriol and Biosyntheses of Bioactive Ginsenosides F1 and Rh1 in Metabolically Engineered Yeasts

Abstract: Ginsenosides, the main pharmacologically active natural compounds in ginseng (Panax ginseng), are mostly the glycosylated products of protopanaxadiol (PPD) and protopanaxatriol (PPT). No uridine diphosphate glycosyltransferase (UGT), which catalyzes PPT to produce PPT-type ginsenosides, has yet been reported. Here, we show that UGTPg1, which has been demonstrated to regio-specifically glycosylate the C20-OH of PPD, also specifically glycosylates the C20-OH of PPT to produce bioactive ginsenoside F1. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 40 publications
2
124
0
1
Order By: Relevance
“…In general, glycosylation is the last step in the biosynthesis of secondary metabolites. Recently, identified eight GTs (UGT73C11, UGT73C10, UGT74AE2, UGT94Q2, UGT71A27, UGTPg1, UGTPg100, UGTPg101) involved in the later steps of ginsenoside biosynthesis in the closely related species P. ginseng 101112.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, glycosylation is the last step in the biosynthesis of secondary metabolites. Recently, identified eight GTs (UGT73C11, UGT73C10, UGT74AE2, UGT94Q2, UGT71A27, UGTPg1, UGTPg100, UGTPg101) involved in the later steps of ginsenoside biosynthesis in the closely related species P. ginseng 101112.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that ginsenoside biosynthesis is achieved mainly through three reaction steps of 2, 3-oxidosqualene: cyclization, hydroxylation and glucosidation7. However, despite these advances, further elucidation of the ginsenoside biosynthetic pathways has been slowed by the limited sequence information available for cytochrome P450 (CYP450) (CYP716A53v2, CYP716A47, CYP716A52v2)89 and glycosyltransferase (GT) (UGT74AE2, UGT94Q2, UGT71A27, UGTPg1, UGTPg100, UGTPg101)101112.…”
mentioning
confidence: 99%
“…Dammarenediol II next is transformed to protopanaxadiol and protopanaxatriol by two cytochrome P450 (CYP) genes (CYP716A47, CYP716A53v2) (Han, Hwang, Choi, Kim, & Choi, ; Han, Kim, Kwon, & Choi, ). Then, protopanaxatriol and protopanaxatriol, transformed by UDP‐glycosyltransferases (UGT) genes UGT94Q2 and UGTpg100 could produce Rh 1 and Rh 2 (Figure S1; Jung et al, ; Wei et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Candidate genes responsible for ginsenoside biosynthesis in the Panax genus have been identified in P. ginseng (Han et al, 2011, 2012; Jung et al, 2014; Kim et al, 2014; Jayakodi et al, 2015; Wang P. et al, 2015; Wei et al, 2015), P. notoginseng (Liu et al, 2015; Rai et al, 2016), and P. vietnamensis (Zhang et al, 2015). Transcriptome analysis of P. notoginseng identified several candidate unigenes encoding cytochrome P450 and glycosyltransferase and revealed that these genes were conserved across all Panax species (Rai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%